Análise de dois métodos radiográficos para avaliação da maturidade esquelética em equatorianos - Calderon, Manuel Estuardo Bravo (2010)
The study of the skeletal development of a certain ethnic group is a relevant scientific contribution that benefits not only orthodontists, but the investigated population itself. The aim of this research was to evaluate skeletal maturation in an Equatorian population sample, by the methods of Hägg and Taranger (1982) and Hassel and Farman (1995). For this purpose, 200 radiographs of the hand and wrist and 200 lateral teleradiographs of patients in the age bracket from 9 to 16 years (100 of girls and 100 of boys), resident in the city of Cuenca, Ecuador, were selected. The images were interpreted by two trained orthodontists, on two different occasions. With the purpose of investigating the reproducibility of the studied methods, the examiners again interpreted 40 radiographs by each method. Cohen’s Kappa statistics were applied in the intra and inter-examiner agreement analyses. Spearman’s Tests were used to analyze the correlation between the interpretations of the two examiners. The correlation between the stages of skeletal maturation, according to each method studied, and chronological age was evaluated by linear regression models. The genders were compared according to categorical variables, in each age group, using the Chi-square test ( = 0.05). Intra-examiner agreement ranged from moderate to high (κ: 0.533-1), while inter-examiner reproducibility was good (κ: 0.734; RS > 0.90; p < 0.001). Directly proportional relationships were found between the chronological age and the stages of maturation determined by hand and wrist radiographs (R2 = 87.7%) and lateral teleradiographs (R2 = 89.6%). There was no dimorphism between the genders. It was concluded that the stages of skeletal maturation determined by the Hägg and Taranger (1982) and Hassel and Farman (1995) methods presented strongly positive correlations with chronological age, and consistency with regard to the behavior of the female and male genders.